Hydrogen Sulfide Reduces Myeloid-Derived Suppressor Cell-Mediated Inflammatory Response in a Model of Helicobacter hepaticus-Induced Colitis - De Cicco, Paola; Sanders, Theodore; Cirino, Giuseppe; Maloy, Kevin J.; Ianaro, Angela (Frontiers in Immunology, 2018)
Chronic inflammation contributes to tumor initiation in colitis-associated colorectal-cancer (CRC). Indeed, inflammatory bowel disease (IBD) patients show an increased risk of developing CRC. Cancer immune evasion is a major issue in CRC and pre-clinical and clinical evidence has defined a critical role for myeloid-derived suppressor cells (MDSCs) that contribute to tumor growth and progression by suppressing T-cells and modulating innate immune responses. MDSCs comprise a heterogeneous population of immature myeloid cells that can be distinct in two subtypes: CD11b+Ly6G+Ly6Clow with granulocytic phenotype (G-MDSCs) and CD11b+Ly6G-Ly6Chigh with monocytic phenotype (M-MDSCs). Hydrogen sulfide (H2S) is an endogenous gaseous signaling molecule that regulates various physiological and pathophysiological functions. In particular, several studies support its anti-inflammatory activity in experimental colitis and ulcer. However, the role of the H2S pathway in innate immune-mediated IBD has not yet been elucidated. To better define a possible link between MDSCs and H2S pathway in colitis-associated CRC development we used an innate immune-mediated IBD model induced by infection with the bacterium Helicobacter hepaticus (Hh), closely resembling human IBD. Here we demonstrated an involvement of MDSCs in colitis development. A significant time-dependent increase of both G-MDSCs and M-MDSCs was observed in the colon and in the spleen of Hh-infected mice. Following, we observed that chronic oral administration of the H2S-donor DATS reduced colon inflammation by limiting the recruitment of G-MDSCs in the colon of Hh-infected mice. Thus, we identify the metabolic pathway L-cysteine/H2S as a possible new player in the immunosuppressive mechanism responsible for the MDSCs-promoted colitis-associated cancer development.